2013
DOI: 10.3168/jds.2012-6401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adjustable and stationary fans with misters on core body temperature and lying behavior of lactating dairy cows in a semiarid climate

Abstract: Cows readily seek shade to reduce solar heat load during periods of high ambient temperature. Typically, auxiliary cooling systems are oriented to maximize cooling for shaded cows. However, when a shade structure is oriented north-south, stationary fan and mister cooling systems are unable to track shade as the sun's angle shifts throughout the day, and thus can become ineffective. The FlipFan Dairy Cooling System (Schaefer Ventilation Equipment, Sauk Rapids, MN) employs fans and misters that follow shade and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 35 publications
1
47
0
6
Order By: Relevance
“…On commercial farms the lying time can be used as a measure of a cow's welfare (Vasseur et al 2012). This is particularly important in the case of heat stress, which reduces the lying time (Anderson et al 2013). It was also confirmed in research performed by Cook et al (2007) in which with increasing of THI the lying time was reduced by 3 h. Along with the deteriorating microclimatic conditions also decreases the locomotor activity (West 2003).…”
Section: Introductionmentioning
confidence: 85%
“…On commercial farms the lying time can be used as a measure of a cow's welfare (Vasseur et al 2012). This is particularly important in the case of heat stress, which reduces the lying time (Anderson et al 2013). It was also confirmed in research performed by Cook et al (2007) in which with increasing of THI the lying time was reduced by 3 h. Along with the deteriorating microclimatic conditions also decreases the locomotor activity (West 2003).…”
Section: Introductionmentioning
confidence: 85%
“…The absence of an effect of access to shade on total time spent standing and lying was unexpected as some studies reported increase in time spent standing to increase heat dissipation by convection (Anderson et al, 2013) while others (Tucker et al, 2008;Schütz et al, 2010) have reported that increased standing time is partly attributed to insufficient cow shade. This was not the case in the present study as cows had more than 10 m 2 each of available shade.…”
Section: Discussionmentioning
confidence: 99%
“…Misting systems were used with good success in the US (Arizona, Kansas, and California) and Saudi Arabia where humidity is typically low [62,63,64,65,66]. Numerous studies [67,68,69,70,71,72,73,74,75] compared the environmental conditions and physiological responses of dairy cows under misters with those obtained under an open-sided barn alone or equipped with fans (Table 6).…”
Section: Methods For Reducing Heat Stressmentioning
confidence: 99%